The Role of Nanomaterials in Plant Production and Fortification for Food and Nutrition Security - Abbey, Lord; Okoli, Chigozie; Martin-Clarke, Deshaun; Ijenyo, Mercy; Abbey , Joel; Anku, Kenneth; Ofoe, Raphael; Leke-Aladekoba, Adedayo; Gunupuru, Lokanadha Rao; Iheshiulo, Ekene Mark-Anthony; Ampofo, Josephine; Abbey, Pretious Anetey (Emerging Challenges in Agriculture and Food Science Vol. 4, 2022)
Fulfilment of global demand for adequate, nutritious, and stable food supply for the growing human population in the face of global climate change is becoming a challenge. As such, there is increasing determination to meet the food needs of the estimated 653 million people that will suffer from poor nutrition by 2030 through the adoption of ‘smart” crop production technology programs. Current manufacturing processes and uses of synthetic agrochemicals have been reported to negatively impact the environment and ecological systems as well as the health and well-being of all life forms. Nanotechnology has been hailed as one of those potential novelties that will help achieve food and nutrition security. As such, the application of nanomaterials with an external size range between 1 and 100 nm to boost crop production has been touted to facilitate the precision delivery of agrochemicals at the appropriate rates. Thus, a promising solution to these challenges is the application of nanotechnology in agricultural production, processing, packaging, and food biofortification. Nanotechnology utilizes biotechnology, biology, and chemical and material engineering principles to construct nanomaterials with extensive but precise applications. Its appropriate use will contribute immensely to increased plant productivity and overall postharvest quality and shelf-life. Despite the many benefits and future opportunities, nanomaterials can pose challenges related to phytotoxicity, the integrity of the environment and ecology, and human health and well-being. This review covers current situation of food and nutrition security, concept of nanotechnology, and potential use of nanomaterials in agriculture for increasing crop productivity and nutrition and dietary benefits. It also focuses on mechanism of action of some major nanomaterials and recent applications in plant science. The perception of nanotechnology among researchers, policymakers, and governments were also reviewed.